P.025 APOLLO, a phase 3 study of patisiran for the treatment of hereditary transthyretin amyloidosis (hATTR): 18-month safety and efficacy in subgroup with cardiac involvement. (5th June 2019) - Vest, J; Solomon, S; Adams, D; Gonzalez-Duarte, A; O'Riordan, W; Yang, C; Coelho, T; Berk, J; Lin, K; Dyck, P; Gandhi, PJ; Sweetser, M; et al.
Abstract : Background: Hereditary transthyretin-mediated (hATTR) amyloidosis a hereditary, multi-systemic and life-threatening disease resulting in neuropathy and cardiomyopathy. In the APOLLO study, patisiran, an investigational RNAi therapeutic targeting hepatic TTR production resulted in significant improvement in neuropathy and QoL compared to placebo and was generally well tolerated.Methods: APOLLO, a Phase 3 study of patisiran vs. placebo (NCT01960348) prespecified a cardiac subpopulation (n=126 of 225 total) that included patients with baseline left ventricular (LV) wall thickness ≥ 13mm and no medical history of aortic valve disease or hypertension. Cardiac measures included structure and function by electrocardiography, changes in NT-proBNP and 10-MWT gait speed.Results: At 18 months, patisiran treatment resulted in a mean reduction in LV wall thickness of 1 mm (p=0.017) compared to baseline, which was associated with significant improvements relative to placebo in LV end diastolic volume (+8.31 mL, p=0.036), global longitudinal strain (-1.37%, p=0.015) and NT-proBNP (55% reduction, p=7.7 x 10-8) (Figure 1). Gait speed was also improved relative to placebo (+0.35 m/sec, p=7.4 x 10-9 ). Rate of death or hospitalization was lower with patisiran. mNIS+7 results in the cardiac subpopulation will also be presented.Conclusions: These data suggest patisiran has the potential to halt or reverse cardiac manifestations of hATTR amyloidosis.